2018
DOI: 10.2169/internalmedicine.0255-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Atrioventricular Block Associated with Pembrolizumab-induced Acute Myocarditis: The Need for Close Cardiac Monitoring

Abstract: Pembrolizumab, a humanized monoclonal IgG4 antibody directed against programmed death-1, is an immune checkpoint inhibitor that has been introduced for the treatment of non-small-cell lung cancer. However, immune checkpoint inhibitors may cause severe immune-related adverse events. We herein present a case of lung cancer with complete atrioventricular block associated with acute myocarditis, which developed 16 days after the administration of pembrolizumab. The clinical course of this case suggested a strong n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…Cardiovascular toxicities are among the rare organ toxicities of ICI therapy [5, 6]. With increased use of ICIs over the past few years, numerous reports of cardiovascular toxicities have emerged (summarized in Table 1, Table 2, Table 3) [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35]. The most serious among them is the development of fulminant myocarditis, a potentially fatal clinical disease which has been the primary focus for the cardio-oncology community [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular toxicities are among the rare organ toxicities of ICI therapy [5, 6]. With increased use of ICIs over the past few years, numerous reports of cardiovascular toxicities have emerged (summarized in Table 1, Table 2, Table 3) [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35]. The most serious among them is the development of fulminant myocarditis, a potentially fatal clinical disease which has been the primary focus for the cardio-oncology community [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently published studies did not find any effects of paclitaxel on cardiac rhythm, which was confirmed by electrocardiography data [24]. Available literature contains a few case reports presenting the cases of complete atrioventricular block development in oncologic patients undergoing chemotherapy, in particular, in a female patient with breast cancer receiving epirubicin and paclitaxel [25] or in a male patient with lung cancer receiving monoclonal antibodies (pembrolizumab) [26].…”
Section: Conflict Of Interestmentioning
confidence: 82%
“…В литературе описаны единичные клинические случаи развития полной атриовентрикулярной блокады у онкологических пациентов, находящихся на химиотерапии, в частности у пациентки с раком молочной железы на фоне приема эпирубицина и паклитаксела [25] или у пациента с раком легкого на фоне приема моноклональных антител (пембролизумаб) [26].…”
Section: Conflict Of Interestunclassified
“…Interestingly, similar to the article by Katsume et al, our patient was receiving pembrolizumab after initial prior treatment with pemetrexed and bevacizumab for NSCLC. Katsume et al's patient was also found to have a high PD-L1 expression of >95% and received pembrolizumab at 200 mg 16 days prior to admission [7]. In other words, both patients were highly susceptible to the effects of pembrolizumab with their tumor cells having a high degree of expression (90% or greater), and both patients developed heart block the second time they received the immunotherapy, approximately 3 weeks after the first infusion.…”
Section: Discussionmentioning
confidence: 98%
“…Immune-related cardiotoxicity is a rare but often fatal complication. Cardiotoxicities associated with pembrolizumab include myocarditis, heart failure, sick sinus syndrome, cardiomyopathy, cardiac fibrosis, and cardiac arrest [3][4][5][6][7]. The following case describes a patient who developed complete heart block which appears to be temporally related to the use of the anti-PD-1 antibody, pembrolizumab.…”
Section: Introductionmentioning
confidence: 99%